(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Acute nephritic syndrome (ANS) is the most common cause of hypertensive heart failure in pediatric population. There are few publications on myocardial evaluation using electrocardiographic and echocardiographic data in pediatric patients with ANS. This study aimed to evaluate myocardial function by electrocardiography and 2-dimensional echocardiography in Egyptian pediatric patients with ANS. Materials and Methods. Sixty children with ANS were included and subjected to clinical, laboratory, electrocardiography for corrected QT interval, and 2-dimensional echocardiographic study on admission, and repeated at 6 and 12 weeks to measure left ventricular ejection fraction, left atrium-aorta ratio, and the ratio of peak early filling (E wave) to late diastolic filling (A wave) velocities (E/A ratio). Results. Prolonged corrected QT interval was reported in 22 patients (36.7%), of whom 18 had hypertension. Fourteen patients (23.3%) had left ventricular ejection fraction below 60%. The same children also had left atrium-aorta ratios more than 2 and E/A ratios more than 2. Left ventricular ejection fraction became within normal values by 6 weeks in 12 patients, and 2 become normal by 3 months of follow-up. 4 of 14 children with low left ventricular ejection fraction (28.6%) had normal arterial blood pressure. All of the 14 children completely recovered within 3 months. Conclusions. Myocardial dysfunction in the acute phase of ANS was alleviated in almost all children within 12 weeks. Although elevated blood pressure was the commonest etiology of congestive heart failure in children with ANS, the impact of primary myocardial functional disturbance could also be put into consideration.